DAMPAK PER-24/PJ/2012 PADA PENERIMAAN NEGARA DARI SEKTOR PAJAK PERTAMBAHAN NILAI (PPN) DAN JUMLAH PENGUSAHA KENA PAJAK YANG MEMBAYAR PPN DI KANTOR PELAYANAN PAJAK PRATAMA BEKASI SELATAN - Vita Aprilina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2016)
This study aimed to determine whether there is statistically different in Value Added Tax Income and the number of VAT Taxable Entrepreneurs in the period before (April 1st 2011 – March 31st 2013) and after (April 1st 2013 – March 31st 2015) the enactment of Per-24/PJ/2012. The sample of this study is all Deposit Letters (Surat Setoran Pajak) and list of taxable entrepreneurs at Bekasi Selatan Tax Office. T-test is used to answer the hypothesis. The results show that there is a difference in Value Added tax Income and the number of VAT Taxable Entrepreneurs that paying VAT for the period before and after the enactment of Per-24/PJ/2012.